The design of a knowledge-based guidance system for an intelligent multiple objective decision support system (IMODSS) - Lu, J.; Quaddus, Mohammed; Poh, K.; Williams, Robert (School of Communications and Information Management, Victoria University of Wellington, 1999)
This paper describes a project that extends the multiple objective decision support system (MODSS) by offering knowledge-based guidance to an intelligent multiple objective decision support system (IMODSS). This IMODSS integrates expert system (ES), multiple objective decision-making (MODM) methodologies, graphical user interface (GUI) and decision support systems (DSS) technologies. This IMODSS uses an expert system shell CLIPS to build a knowledge base to guide the decision-makers (DMs) to select the most suitable MODM method(s) from the MODM methodology base in order to solve their particular decision problems. This IMODSS has been implemented and tested. This paper mainly discusses the design and implementation of the knowledge-based intelligent guidance subsystem in IMODSS.